Pengaruh Keterampilan Komunikasi Interpersonal dan Kepercayaan Diri terhadap Workforce agility Siswa SMK Negeri se-Kecamatan Semarang Selatan - Fita Prestiyani; Maria Theresia Sri Hartati; Achmad Miftachul 'Ilmi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In the era of disruption, characterized by rapid technological advancements, shifting industrial demands, and the transformation of job types that require adaptive skills, competencies such as workforce agility have become crucial for vocational school graduates. This study aims to examine the influence of interpersonal communication skills and self-confidence on workforce agility among students of Vocational High Schools (SMK) in South Semarang District. Employing a quantitative correlational approach, the research involved 266 twelfth-grade students from five public vocational schools in the district, selected through stratified random sampling. Validity and reliability tests confirmed that all instruments were reliable (Cronbach’s Alpha > 0.60). Descriptive analysis indicated that most students were in the moderate category across all three variables. Hypothesis testing revealed that interpersonal communication skills significantly influenced workforce agility (R = 0.630; F(1, 264) = 173.951; p < 0.001), with the “sender-receiver” indicator contributing the most. Similarly, self-confidence significantly affected workforce agility (R = 0.643; F(1, 264) = 186.035; p < 0.001), with “objectivity” being the most influential indicator. When tested simultaneously, both variables had a significant combined influence on workforce agility (R = 0.708; F(2, 263) = 132.257; p < 0.001). These findings suggest that strengthening interpersonal communication and self-confidence plays a vital role in enhancing students' agility in navigating the evolving demands of the labor market. Future research is encouraged to explore additional psychological and contextual factors that may contribute to workforce agility, in order to enrich both theoretical understanding and practical efforts in preparing students for the dynamic employment landscape.